The association of sexual dysfunction with race in women with gynecologic malignancies - M. Frimer; L.B. Turker; V. Shankar; R. Cardaci; A.R. Van Arsdale; E. Rosenthal; D.Y.S. Kuo; G.L. Goldberg; N. Nevadunsky (Elsevier, 2019)
Gynecologic cancer survivors report sexual health among their highest concerns. The aim of this study was to identify the prevalence of sexual dysfunction (SD) in survivors of gynecologic malignancies and to evaluate the association of sexual function with race, ethnicity and treatment modality. In this study, survivors of endometrial, cervical, vaginal, and vulvar cancer who presented to the gynecologic oncology practice were asked to self-administer the Female Sexual Function Index (FSFI) survey to evaluate their sexual function. The prevalence of SD was estimated and its association with demographic and clinical co-variates was analyzed. Of the 155 participants, the prevalence of SD was 44.5% (95%CI: 36.7-52.7). Patients were significantly more likely to report SD if they did not currently have a partner (69% vs 22% p < .01). Abstinence within six months of their cancer diagnosis was also associated with SD (72% vs 26% p < .01). Patients who self-identified as black race compared to white race were three times more likely to have SD (OR = 3.9, 95% CI 1.1-14.3). Patients who received adjuvant chemotherapy and radiation therapy compared to those who did not among the entire cohort had an increased risk of SD (OR = 3.4, 95% CI 1.2-9.6). In our diverse population, almost half of our patients were identified to have SD. Black as compared to white race reported significantly higher sexual dysfunction. An increased risk for sexual dysfunction was observed among those women who received chemotherapy and radiation with or without surgery. Precis: Survivorship is an important issue for women with gynecologic malignancies. This study addresses the high rates of sexual dysfunction in a racially diverse patient population.